β-Hydroxybutyrate alleviates cartilage senescence through hnRNP A1-mediated up-regulation of PTEN - Guang Xia; Zi Wen; Lina Zhang; Junjie Huang; Xinxing Wang; Chi Liang; Xiaoyu Cui; Xu Cao; Song Wu (Experimental Gerontology, 2023)
Senescence chondrocytes play an important role in Osteoarthritis (OA) progression. However, alleviating OA progression through senescent chondrocyte intervention still faces great challenges. β-Hydroxybutyrate (BHB) exhibits anti-senescence effects in a variety of age-related dis-eases, but its role in osteoarthritis remains poorly understood. To explore the molecular mechanisms, gene sequencing was used to identify critical genes and potential cellular signaling pathways and male SD rats were used to generate an osteoarthritis model. Results showed that BHB attenuated the senescence of Osteoarthritis chondrocytes (OA-Chos) and alleviated OA progression. Gene ontology (GO) enrichment analysis revealed significant changes in cell cycle genes, with PTEN being the most significant differentially expressed gene. BHB up-regulated the expression of PTEN in OA-Chos, thereby alleviating chondrocyte senescence. Furthermore, BHB facilitated the expression of PTEN by binding to hnRNP A1 and inhibiting the phosphorylation of Akt. This study provided evidence that BHB mitigated chondrocyte senescence and delayed OA, and could thus be used as a novel therapeutic approach for osteoarthritis treatment.